Abundance of Оpisthorchis felineus larvae in cyprinid species in the West Kazakhstan Region - F. Kh. Nurzhanova; R. S. Karmaliyev; G. G. Absatirov; E. M. Sengaliyev (Российский паразитологический журнал, 2021)
The purpose of the research is studying the abundance of Opisthorchis sp. in cyprinid fish.Materials and methods. Diagnostic studies of fish are aimed at identifying the larval stages of Opisthorchis sp. – metacercariae that are infective for carnivores and humans. We examined 183 specimens of fish that belong to 7 species. The fish were examined by the compression method under an MBS-9 microscope.Results and discussion. The epidemiologically and epizootologically significant fish species in the West Kazakhstan Region are the ide, rudd, roach, bream, tench and silver bream. The infection rate of cat liver fluke metacercariae in these fish species is an indicator of the contamination of the region. The highest prevalence and intensity of infection are recorded in the ide. When studying the age dynamics of fish infected by Opisthorchis sp. metacercariae, we found an increase in infection rate with age. This is the result of a gradual annual accumulation of the parasite in the host. The greatest localization of metacercariae in the fish was observed in the muscles near the dorsal fin where the proportion of accumulated larvae was more than 90%.